2019
DOI: 10.3748/wjg.v25.i31.4512
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of esophageal cancer in Africa: Epidemiology, risk factors, management and outcomes

Abstract: BACKGROUND Esophageal cancer (EC) is associated with a poor prognosis, particularly so in Africa where an alarmingly high mortality to incidence ratio prevails for this disease. AIM To provide further understanding of EC in the context of the unique cultural and genetic diversity, and socio-economic challenges faced on the African continent. METHODS We performed a systematic review of studies from Africa to obtain data on epidemiology, risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 113 publications
8
69
1
Order By: Relevance
“…Our results showed that, in general, men had a higher mortality rate of esophageal and lung cancer and that this rate increases with age. In fact, the scientific literature corroborates these results [26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 56%
“…Our results showed that, in general, men had a higher mortality rate of esophageal and lung cancer and that this rate increases with age. In fact, the scientific literature corroborates these results [26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 56%
“…While EC is the leading cause of cancer mortality in men in Kenya, it has been shown to have the highest global incidence in both men and women in Malawi. 3,12 These patients may remain clinically asymptomatic for a long time. If the disease progresses, it can lead to complaints, such as weight loss and dysphagia.…”
Section: Esophageal Cancer (Ec)mentioning
confidence: 99%
“…Esophageal cancer ranked seventh in incidence with an estimated 572,000 new cases and sixth in mortality overall with 509,000 deaths in 2018 worldwide. The reasons for increased incidence of cases of esophageal cancers are multiple but generally reflect both aging and growth of the population, changes in lifestyles including smoking, alcohol intake, and obesity, as well as changes in the prevalence and distribution of the main risk factors for cancers in general [ 1 3 ]. Esophageal cancer is quite common in South East Asia and Eastern Africa.…”
Section: Introductionmentioning
confidence: 99%